(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In Vimana Sthana, Acharya Charaka has mentioned that there are several types and method of examination (Ch. Vi. 8/81). It is absolutely essential to select the method which one is easy, possible and most suitable practically in all respects with least flows. For that Charaka has advised Dashavidha Pariksha i.e. Kaarana, Karan etc. Planning for research should be based on these guidelines. Out of this Karan or medicine is most important for clinical trial. Amavata is most common disease among various joints disorders and the changing life style and dietetic pattern are also being manifested as the increment in the number of patient day by day. Ample amount of research work has been done on the disease Amavata. In Ayurvedic literature, numbers of herbal preparation are described for the management of the disease. Here to assess the efficacy of Rasna and Nirgundi and to compare the effect of these two therapies a clinical study has been designed. The first section designated as literary review deals with the drug review at the outset discusses the reasoning behind selection of the drugs under trial. Thereafter the pharmacodynamics of each individual drug are explained.